Developments in the Implementation of Corporate Governance in Initial Public Offerings (IPO) - Paramita, Ratih Prajna; Kusuma, Poppy Dian Indira (Riwayat: Educational Journal of History and Humanities, 2023)
This literature review aims to discuss the impact of effective corporate governance on implementation developments for companies conducting initial public offerings (IPOs) on the Indonesia Stock Exchange. Based on good corporate governance practices in Asia, Indonesia is a low-ranking company, so this study uses 10 variables approved by the Indonesian Ministry of Research and Technology. Good corporate governance variables include committees, independent committees, board of directors, directors, board of directors and independent directors. The test used as a method is a systematic literature search. The results of this study show empirical evidence in a review that the effectiveness of corporate governance has a positive and negative effect on underpricing.